Interaction between gut microbiota and T cell immunity in colorectal cancer - Jing, Zhuang; Yinhang, Wu; Jian, Chu; Zhanbo, Qu; Xinyue, Wu; Shuwen, Han (Autoimmunity reviews, 2025)
This review delves into the complex and multi-layered mechanisms that govern the interaction between gut microbiota and T cells in the context of colorectal cancer (CRC), revealing a novel “microbiota-immune regulatory landscape” within the tumor microenvironment. As CRC progresses, the gut microbiota experiences a significant transformation in both its composition and metabolic patterns. On one hand, specific microbial entities within the gut microbiota can directly engage with T cells, functioning as “immunological triggers” that shape T-cell behavior. Simultaneously, microbial metabolites, such as short-chain fatty acids and bile acids, serve as “molecular regulators” that intricately govern T-cell function and differentiation, fine-tuning the immune response. On the other hand, the quorum-sensing mechanism, a recently recognized communication network among bacteria, also plays a pivotal role in orchestrating T-cell immunity. Additionally, the gut microbiota forms an intriguing connection with the neuro-immune regulatory axis, a largely unexplored “territory” in CRC research. Regarding treatment strategies, a diverse array of intervention approaches—including dietary modifications, the utilization of probiotics, bacteriophages, and targeted antibiotic therapies—offer promising prospects for restoring the equilibrium of the gut microbiota, thereby acting as “ecosystem renovators” that impede tumor initiation and progression. Nevertheless, the current research landscape in this field is fraught with challenges. These include significant variations in microbial composition, dietary preferences, and tumor microenvironments among individuals, a lack of large-scale cohort studies, and insufficient research that integrates tumor mutation analysis, gut microbiota investigations, and immune microenvironment evaluations. This review emphasizes the necessity for future research efforts to seamlessly incorporate multiple factors and utilize bioinformatics analysis to construct a more comprehensive “interactive map” of the gut microbiota-T cell relationship in CRC. The aim is to establish a solid theoretical basis for the development of highly effective and personalized treatment regimens, ultimately transforming the therapeutic approach to CRC.